The Effect of Dysmenorhore Exercises with Traditional Kalimantan Music in Reducing the Scale of Pain in Adolescents - Endras Amirta Hanum; Nur Afni Shafina (Indonesian Journal of Global Health Research, 2024)
Dysmenorrhea occurs because the endometrium contains high amounts of prostaglandins which have an impact on the systemic response, which can affect various processes in the body, one of which is increasing the activity of the large intestine, causing symptoms of nausea, diarrhea, headaches, emotional changes and a burning sensation that accompanies pain during menstruation. The impacts that occur if dysmenorrhea is not treated are disruption of daily life activities, Retrograde menstruation (menstruation that moves backwards), infertility (sterility) and infection. In addition to the above impacts, emotional conflict, tension and anxiety can all play a role and cause feelings of discomfort and unfamiliarity. Tension usually worsens a bad situation at any time. A little discomfort quickly develops into a big problem with all the annoyance that accompanies it. Thus anxiety, feelings of unhappiness or even feelings of pressure are all not uncommon. Therefore, dysmenorrhea must be treated so that impacts such as the above do not occur. The nature and degree of this pain vary, from mild to severe. This research is quasi-experimental with a non-equivalent design with control group (two group pre test – post test). The population of all female students at SMA Nusantara Class I and II is 61 people, with a sample of 19 people taken using simple random sampling. The measuring tool for identifying dysmenorrhea uses a numerical pain scale. The treatment given is dysmenorrhea exercises with Traditional Kalimantan Music 3 times in a row a week before the female students menstruate, efore conducting the t-test, a normality test was conducted to determine whether the data was normally distributed or not. The Shapiro-Wilk test was used. The results obtained from the p-value normality test are 0.96, because the p value > 0.05 then the data is normally distributed. So the data for both groups are equally normally distributed. The mean pain scale before the intervention was given in the treatment group was 5.89 (moderate pain), in the control group it was 5.33 (moderate pain) while the mean pain scale after dysmenorrhea exercises in the treatment group was 2.33 (mild pain) and in the the control group was 5.0 (moderate pain). Statistical test analysis using the Independent T-test showed that the p-value was 0.006 < α=0.05, indicating that there was a significant influence of dysmenorrhea exercise on reducing dysmenorrhea in class I and II female students at SMA Nusantara Balikapapan. Doing dysmenorrhea exercises 3 times in a row a week before menstruation can reduce pain in female students. So it is necessary to encourage women who experience dysmenorrhea to do dysmenorrhea exercises with Traditional Kalimantan Music.